Surgical Management of Aural Haematoma in a Rabbit - A Case Report - Amith, G.; Shruthi, J. S.; Priya, P.; Pramodh, J.K.; Chandrashekar , T. (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
Aural haematoma is the collection of blood or serum within the cartilage plate of the ear pinna which presents as fluctuant, fluid-filled swelling on the concave surface of one or both the pinna (Fossum, 2007). It occurs as a result of constant shaking and rubbing of ear due to otitis, ectoparasitism, ottorrhoea, foreign bodies, hypersensitivity and allergic dermatitis. This chronic irritation, constant shaking and rubbing of the ear leads to rupture of the pinnal blood vessel resulting in haematoma formation (Ahiwar et al., 2007).